Navigating digital risks and benefits: Malaysian parents' perceptions of their children's digital media usage - Shafizan Mohamed,; Wan Norshira Wan Ghazali,; Nur Shakira Mohd. Nasir, (Penerbit Universiti Kebangsaan Malaysia, 2024)
In this article, we explore how Malaysian parents view their children's use of digital media. We studied 645 parents from various backgrounds to understand how they navigate the world of digital devices and content. Our research dives into the fine line parents walk between what they see as the risks and the benefits in this digital landscape. What we discovered is that these parents have a pretty nuanced view. They see the positives—like how digital media can boost education, improve communication, and expose their kids to diverse cultures. But at the same time, they worry. They're concerned about things like too much screen time, exposure to inappropriate stuff, and how it might affect their kids' physical activity. Our study found that different things influence how parents see these issues. Factors like how much education parents have, how much they earn, and the ages of their kids play a role in shaping their views. With Malaysia becoming more and more digital, our research aims to help policymakers, teachers, and parents themselves. By getting a handle on what worries and excites parents about digital media, we hope to find ways to make it work better for everyone. Our goal is to figure out how to make the most of the good stuff digital media offers while finding ways to deal with the concerns. Ultimately, we want to create a digital world that's healthier and more balanced for Malaysian kids.